Effects of Several Organic Fertilizers on Heavy Metal Passivation in Cd-Contaminated Gray-Purple Soil - Wang, Luyao; Liu, Siqi; Li, Jianfeng; Li, Shunqi (Frontiers in Environmental Science, 2022)
Soil heavy metal pollution has become a major ecological and environmental problem and a serious threat to global food security. Organic fertilizer can not only improve soil quality and provide nutrients for plants but also reduce the harm of heavy metal ions to a certain extent, meaning it has become a current research hotspot in the field of heavy metal passivation. In this paper, a completely combined experimental design was used to compare the effects of five organic fertilizers [nutshell organic fertilizer (NOF), pig manure organic fertilizer (PMOF), sludge organic fertilizer (SOF), humus soil organic fertilizer (HSOF) and earthworm soil organic fertilizer (ESOF)] on available Cd in soil with different pollution levels at different dosages, and the passivation mechanism of soil Cd was preliminarily discussed. The results showed that all kinds of organic fertilizers were passivated by reducing the Cd availability, and their effects on the Cd availability of purple soil were closely related to the degree of soil pollution and the amount of organic fertilizers. The passivation effect of moderate Cd-contaminated soil was the best, which increased with the increase of organic fertilizer application rate, and the effects of NOF and SOF were the best. However, the passivation effect of organic fertilizers on soil Cd was the worst in mild Cd-contaminated soil, especially ESOF. The results of Cd morphological correlation analysis showed that Exe-Cd and FeMnOx-Cd in the soil had significantly positive contributions to available Cd, while Res-Cd showed significantly negative contributions. And in moderate Cd contaminated soil, Exe-Cd content decreased by 7.12%–28.50%, while Res-Cd content increased by 19.74%–65.81%. In addition, the content of available Cd in soil decreased first and then increased with time after adding organic fertilizer, and reached the lowest value at 15 days and stabilized after 60 days. The conclusion of this paper can provide a theoretical basis for the rational use of organic fertilizer to reduce the bioavailability of cadmium in Gray-Purple soil.